Estimating the rate of re-expansion of spontaneous pneumothorax by a formula derived from computed tomography volumetry studies. Issue 10 (20th September 2006) - Kelly, A-M; Loy, J; Tsang, A Y L; Graham, C A
Abstract : Background: Available evidence suggesting that the rate of re-expansion of spontaneous pneumothorax is 1.25%/day is based on a small sample and mathematical modelling-based estimates. Aim: To estimate the rate of re-expansion of spontaneous pneumothoraces by a formula derived from computed tomography volumetry studies. Methods: This retrospective study included adult patients with spontaneous pneumothorax, identified from patient management databases, who were treated conservatively. Medical records were reviewed to confirm that no intervention such as aspiration or catheter drainage had occurred. Radiographs were reviewed independently by two researchers and measured according to the method described by Collins et al . Their formula was used to estimate pneumothorax size on each date. The rate of re-expansion was defined as the change in size (%)/number of days between radiographs. Patients were excluded if they did not have at least two radiographs taken, at least 1 day apart. Data were analysed using cluster analysis by patient to minimise the effect of repeated measures from an individual patient. Results: 88 episodes were identified in 57 patients. 82% were men and the patients had a median age of 22 years. The average rate of re-expansion was 2.2%/day (95% confidence interval 1.4% to 3.0%), but varied between −7.5% and 13.4%/day. Conclusion: Spontaneous pneumothoraces treated conservatively re-expand at an average rate of 2.2%/day.